2014
DOI: 10.1084/jem.20130062
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils are required for both the sensitization and elicitation phase of contact hypersensitivity

Abstract: Weber et al. report that neutrophils are required for both the sensitization and elicitation phase of contact hypersensitivity. Their results identify a novel role for neutrophils in shaping the adaptive immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
151
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 159 publications
(171 citation statements)
references
References 28 publications
11
151
0
4
Order By: Relevance
“…In agreement with our findings, novel results of a recent study established the requirement of neutrophils for the development of sensitization during CHS 15 . The study also revealed that hapten 2,4,6-tri nitrochlorobenzene-induced sensitization subsequent to the CHS response was impaired in antibody (NIMP-R14)-mediated neutrophil-depleted mice due to suppression of IFN-γ production (derived from skin dLN cells) and DC migration to the dLN 15 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our findings, novel results of a recent study established the requirement of neutrophils for the development of sensitization during CHS 15 . The study also revealed that hapten 2,4,6-tri nitrochlorobenzene-induced sensitization subsequent to the CHS response was impaired in antibody (NIMP-R14)-mediated neutrophil-depleted mice due to suppression of IFN-γ production (derived from skin dLN cells) and DC migration to the dLN 15 .…”
Section: Discussionsupporting
confidence: 93%
“…The study also revealed that hapten 2,4,6-tri nitrochlorobenzene-induced sensitization subsequent to the CHS response was impaired in antibody (NIMP-R14)-mediated neutrophil-depleted mice due to suppression of IFN-γ production (derived from skin dLN cells) and DC migration to the dLN 15 . However, our findings indicate that DNFB-induced CHS in the neutrophil depletion caused by the 1A8 antibody did not abrogate IFN-γ production.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…At the site of infection/inflammation, neutrophils use an armamentarium of effector functions, including phagocytosis, respiratory burst, degranulation and neutrophil extracellular trap (NET) formation to eliminate the invading microorganisms [6,7]. In addition, neutrophils also participate in the organization of the overall immune response [6][7][8][9]. Despite being short-lived, terminally differentiated cells with limited transcriptional activity, they can undergo stimulus-induced gene expression changes leading to chemokine and cytokine release into the extracellular space [6,10,11].…”
Section: Overview Of Feedback Amplification Of Neutrophil Functionmentioning
confidence: 99%
“…Using one Kit-independent MC-deficient strain, Dudeck et al reported evidence that MCs amplify rather than limit CHS responses, and concluded that the exaggerated CHS reactions observed in Kit-mutant animals are not caused by the absence of MCs but instead reflect other effects of the KIT deficiency (7,13). By contrast, based on findings in both Kit-mutant and Kit-independent MC-deficient mice, Gimenez-Rivera et al recently reported that MCs can suppress skin inflammation in a new mouse model of chronic CHS (14).…”
Section: Introductionmentioning
confidence: 99%